OPTIMATISASI PEMANFAATAN DANA WAKAF MELALUI PERUSAHAAN ASURANSI SYARIAH - Ani Faujiah (ICO EDUSHA, 2020)
Waqf insurance benefits and investment in sharia life insurance may follow the provisions contained in the fatwa. The concept of waqf in insurance is divided into three types. First, the Wakaf Fund, a waqf as an insurance model, in which Tabarru funds in sharia insurance called waqf funds. The mechanism, before people tabarru, the company formed a waqf fund, then people tabarru and tabarru funds were put into the fundwakaf fund. Second, Wakaf Polis is a policy that is ready and in the hands of policyholders, the benefits are pledged to the agency or waqf institution. Policies received by waqf agencies or institutions come from conventional and sharia insurance. The relevance of waqaf and sharia insurance aims to the utilization of insurance by investing through waqf management institutions that later have results and benefits, then those benefits can be used for the benefit of the people. This research uses phenomenological qualitative approach, because qualitative approach has characteristics, among others: it has actual settings, researchers become key instruments, data is usually descriptive, emphasizes the process, data analysis is inductive, and meaning (meaning) of each event is an essential concern. The technique used to observe the activities in Islamic financial institutions is engaged in insurance and waqf as an important actor in wealth distibusi Keywords: waqf, Sharia insurance, Islamic financial institutions